The Rule of Law as Independent Political Ideal - Melero de la Torre, Mariano (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The contemporary debate about the rule of law assumes an apparently inevitable dilemma: either we conceive this ideal as merely instrumental and therefore independent of any substantive political morality, or we devise it as a non-instrumental ideal and, thereupon, as tied to a specific theory of justice. This paper aims to offer an alternative, which is called the “formal-constitutional conception”, where legality appears as an independent and, simultaneously, intrinsically valuable political ideal. On the path of Lon Fuller, this conception consists of a number of procedural requirements that do not determine the content of the legal norms, but serve as a moral tribunal in which the positive law is accountable.
Keywords: Legality; rule of law; constitutionalism; democracy; positivism; theory of justice; publicity; accountability